SmartStartAllergy: a novel tool for monitoring food allergen introduction in infants. Issue 6 (25th January 2020) - O'Sullivan, Michael; Vale, Sandra; Loh, Richard KS; Metcalfe, Jessica; Orlemann, Karin; Salter, Sandra; Peters, Ian; Leeb, Alan
Abstract: Objectives: To estimate the proportion of infants introduced to peanut and other common food allergens by 12 months of age; to collect information about parent‐reported reactions to food. Design, setting: Observational cohort study, applying the SmartStartAllergy SMS protocol and online questionnaire to parents of 12‐month‐old infants attending 69 Australian general practices between 21 September 2018 and 3 May 2019. Participants: 3374 parents recruited via the 69 participating general practices. Main outcome measures: Proportions of infants who had eaten peanut and other common food allergens; proportions with parent‐reported reactions to food. Results: 1940 of 3374 invited parents participated in the study (response rate, 57%), of whom 836 (46%) completed the online questionnaire. At 12 months of age, 1673 of 1940 infants had eaten peanut‐including foods (86.2%; 95% confidence interval [CI], 84.6–87.7%); 235 of 1831 parents (12.8%; 95% CI, 11.3–14.5%) reported food‐related reactions. Questionnaire responses indicated that dairy was the food type most frequently reported to cause a food‐related reaction (72 of 835 exposed infants, 8.6%; 95% CI, 6.8–11%); peanut‐related reactions were reported for 20 of 764 exposed children (2.6%; 95% CI, 1.6–4.0%). 97 of 250 parent‐reported reactions to food (39%) did not include symptoms that suggested an IgE‐mediated allergic reaction. Conclusion: Infant feeding practices in Australia have changed over the past decade; a large majority of infants are now fed peanut before 12 months of age. The SmartStartAllergy program allows monitoring of infant feeding practices in primary care, as well as of parent‐reported reactions to food in infants.